(untitled) (INTERNATIONAL SEMINAR, 2023)
As the Federal Funds Rate (Fed Rates) reached a new series of hikes throughout the year 2022-2023, new studies that aim to investigate the effect of such a hike have been developed in the monetary realm. The act was initiated to tame the inflation rate in the U.S. Federal Open Market Committee’s (FOMC) meetings, which resulted in rising Fed Rates repeated several times. As shown in previous studies, the adjustment in U.S. monetary policy affected Asian Countries monetarily. Although only a few studies have yet to research the Fed Rate’s effect on Indonesia’s central bank interest rate, commonly called B.I. 7DRRR (Bank Indonesia 7 Days Reverse Repo Rate). In line with that, this research aims to analyze the impact of recent Fed Rate hikes in 2022-2023 to B.I. 7DRRR. The research was conducted using both meta-analyses on previous studies using secondary data, on variables such as Fed Rates and BI7DRRR, and using VAR (Vector Autoregression) simultaneously. The result showed that Fed Rates did affect BI7DRRR significantly through the increased rate of BI7DRRR equivalent with the Fed Rates’ hikes.